The relationship between happiness & religiosity among instead students through utilization of 'the happi-reli scale' and its validation - Othman, Joharry; Mamat , Arifin; Awang Mat , Muhamad Zahiri (IIUM Press, 2009)
This study attempts to investigate two constructs that are important in everyday lives. The constructs are "happiness" and "religiosity". Since the study of such constructs have been numerous in western literature and the idea of "positive psychology" is being embraced in most current educational field, the researcher felt compelled to embark on this study. 200 Institute of Education, IIUM students formed the sample of this study and they were given to respond to a questionnaire titled "Happi-Reli Scale" that consisted of 60 items. Apart from the findings that confirmed the results from the precious studies involving these constructs (religiosity, happiness, spirituality, well being, etc) using statistical analyses, the study also found a third factor (besides happiness & religiosity) based on data analysis of the results.